Determination of hexane residues in vegetable oils in FTIR spectroscopy - Mirghani, Mohamed Elwathig Saeed; Che Man, Yakoob (Springer Berlin, 2003)
An FTIR spectroscopy method was developed for the determination of hexane residues in palm and groundnut (peanut) oils. The method was based on horizontal attenuated total reflectance with a ZnSe crystal at 45° at room temperature, and partial least squares (PLS) statistics were used to derive calibration models. The accuracy of the method was comparable to that of the AOCS Method Ca 3b-87, with coefficients of determination (R2) of 0.9866 and 0.9810 for palm and groundnut oils, respectively, and SE of calibration of 3.83 and 4.91, respectively. The calibration models were validated, and the R2 of validation and the SE of prediction computed. The SD of the difference for repeatability for the method was comparable to that for the standard AOCS method when used for palm and groundnut oils. With its speed and ease of data manipulation by computer software, FTIR spectroscopy has an advantage over present chemical methods, which require preparation of the oil using toxic solvents before GC.